Lung Ultrasound Characteristics in Neonates With Positive Real Time Polymerase Chain Reaction for SARS-CoV-2 on a Tertiary Level Referral Hospital in Mexico City - Ibarra-Ríos, Daniel; Enríquez-Estrada, Andrea Constanza; Serpa-Maldonado, Eunice Valeria; Miranda-Vega, Ana Luisa; Villanueva-García, Dina; Vázquez-Solano, Edna Patricia; Márquez-González, Horacio (Frontiers in Pediatrics, 2022)
Introduction: Acute respiratory syndrome secondary to SARS-CoV-2 virus infection has been declared a pandemic since December 2019. On neonates, severe presentations are infrequent but possible. Lung ultrasound (LUS) has shown to be useful to diagnose lung involvement and follow up patients, giving more information and reducing exposure compared to traditional examination. Methods: LUS was performed after the diagnosis of SARS-CoV-2 infection with respiratory RT-PCR with portable equipment protected with a silicone sleeve (Konted™, Beijing China, Linear 10.0MHz). If Hemodynamic or Cardiology consultation was necessary a prepared complete ultrasound machine (Vivid™ E90, GE Medical Systems, Milwaukee, WI, USA with a hockey stick probe 8-18 MHz) was used. 10 regions were explored (anterior superior and inferior, lateral, and posterior superior and inferior, right and left) and a semiquantitative score (LUSS) was calculated. Results: 38 patients with positive RT-PCR were admitted, of which LUS was performed on 32 (81%). Included patients had heterogenous diagnosis and gestational ages as expected on a referral NICU (median, ICR: 36, 30-38). LUS abnormalities found were B line interstitial pattern 90%, irregular/interrupted/thick pleural line 88%, compact B lines 65%, small consolidations (≤5 mm) 34% and extensive consolidations (≥5 mm) 37%. Consolidations showed posterior predominance (70%). LUSS showed a median difference between levels of pulmonary support (Kruskal-Wallis, p=0.001) and decreased with patient improvement (Wilcoxon signed rank test p=0.005). There was a positive correlation between LUS score and FiO2 needed (Spearman r=0.72, p=0.01). The most common recommendation to the attending team was pronation (41%) and increase in positive end expiratory pressure (34%). Five patients with comorbidities died. A significant rank difference of LUSS and FiO2 needed between survivors and non survivors was found (Mann-Whitney U test, p=0.005). 26% of discharged patients showed an enlarged thymus. Conclusions: LUS patterns found were like the ones described in other series (neonatal and pediatrics). While there is no specific pattern, and it varies according to gestational age and baseline diagnosis LUS showed to be useful to assess lung involvement that correlated with the degree of respiratory support.